Response of Growth and Yield of Short-Straw Wheat (Triticum aestivum L.) to Salinised Water and Cycocel (CCC). - ASSEED, MOHAMED; SOROUR, F. A.; EL-SHARKAWY, M. A. (The Libyan Journal of Agriculture, 2023)
The influence of irrigation with salinised water, with and without CCC treatments, on growth and yield of the short-straw wheat variety ‘Sidi El-Misri, was investigated under greenhouse conditions. Seedling emergence was delayed by increasing salinity. Plant height at early stage was also reduced. Cycocel application significantly reduced plant height. No significant effects on grain yield and various yield components were observed due to CCC treatment. On the other hand, irrigation with up to 6,000 ppm salinised water increased grain yield per plant as well as other yield components. Straw yield was significantly reduced by salinity therefore resulting in higher grain to straw ratio. Wheat plants tolerated salinity level up to 6,000 ppm irrespective of CCC application.